Transaction Costs: Prosecuting child trafficking for illegal adoption in Russia - McCarthy, Lauren A (Anti-Trafficking Review, 2016)
As primary implementers of laws on human trafficking, law enforcement helps construct how these laws are understood and applied. This article examines how this process has unfolded in Russia by looking at the phenomenon of and debates surrounding child trafficking for illegal adoption. It argues that pre-existing experience with trafficking laws and cultural narratives surrounding adoption have led law enforcement to focus on uncovering evidence of monetary transactions rather than exploitation when prosecuting trafficking cases. This construction of the meaning of trafficking comes with important trade-offs. While the emphasis on transactions helps law enforcement to be successful at prosecuting cases involving selling children for illegal adoption, a focus on transactions rather than exploitation results in a de facto prosecution policy that ignores the many forms of exploitation that occur in other trafficking cases.